Logos Abadi dalam Kefanaan:Eksplorasi Kristologi Identitas Ilahi dalam Pengkhotbah 3:11 - Refamati Gulo; Syalom Denish Imanuell Sahapudi (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
This study explores the Christological dimension of Ecclesiastes 3:11 through a systematic hermeneutical approach to the concept of divine wisdom in the Old Testament context. The focus of the analysis is on the phrase “He put eternity in their hearts” as a starting point for the prefiguration of the concept of Logos in John's Gospel. By combining Hebrew textual studies, intertextual studies with New Testament Christological texts, and systematic theological synthesis, this study puts forward four main findings: (1) the term haolam in Ecclesiastes 3:11 exhibits a conceptual relationship with the Logos; (2) the anthropological structure in the phrase provides the basis for the reception of Christological revelation, formulated as the “principle of ontological correspondence”; (3) the tension between temporality and eternity in the text anticipates the paradox of the incarnation; and (4) a dialectical structure is found in the passage that parallels the pattern of classical Christology. Overall, this study contributes a new hermeneutical model to Ecclesiastes in the light of Christology, and introduces the framework of a “theology of temporal beauty” as an attempt to bridge between the beauty of time and the reality of the incarnation.     Penelitian ini mengeksplorasi dimensi kristologis dari  Pengkhotbah 3:11 melalui pendekatan hermeneutik sistematis terhadap konsep hikmat ilahi dalam konteks Perjanjian Lama. Fokus analisis tertuju pada frasa “Ia menaruh kekekalan di dalam hati mereka” sebagai titik awal prefigurasi terhadap konsep Logos dalam Injil  Yohanes. Dengan memadukan kajian tekstual Ibrani, studi intertekstual dengan teks-teks Kristologis Perjanjian Baru, dan sintesis teologis sistematis, penelitian ini mengemukakan empat temuan utama: (1) istilah haolam dalam  Pengkhotbah 3:11 memperlihatkan hubungan konseptual dengan Logos; (2) struktur antropologis dalam frasa tersebut memberikan dasar bagi penerimaan wahyu Kristologis, dirumuskan sebagai “prinsip korespondensi ontologis”; (3) ketegangan antara temporalitas dan kekekalan dalam teks ini mengantisipasi paradoks inkarnasi; dan (4) ditemukan struktur dialektis dalam ayat ini yang sejajar dengan pola kristologi klasik. Secara keseluruhan, penelitian ini menyumbangkan model hermeneutika baru terhadap  Pengkhotbah dalam terang Kristologi, serta memperkenalkan kerangka “teologi keindahan temporal” sebagai upaya menjembatani antara keindahan waktu dan realitas inkarnasi.